The impact of energy security risks on energy consumption. (2018) - Tolliver, Clarence; Islam, Moinul; Shin, Kong Joo; Managi, Shunsuke
This study assesses the impact of energy security risks on energy consumption by analysing a panel of data from 64 countries from 1980 to 2014. We find that rising energy security risk increases oil, natural gas, nuclear power, and wind power consumption and decreases hydroelectric power consumption. We also find that countries with greater energy security risks have increased the relative share of wind energy in their total energy consumption. These results suggest that energy security risk leads to diversified energy consumption through the adoption of renewable energy technologies. Furthermore, gross domestic product and population growth also result in overall increases in the energy consumption levels. This result is consistent with the results found in the existing literature. However, when we analyse the consumption of specific energy sources, solar and wind power consumption levels are shown to decrease in response to population growth.